(untitled) (Hoboken, N.J., 2007)
Although not a game in the strictest sense of the word, the increasingly popular virtual world of Second Life shares many commonalities with online gaming environments. Libraries interested in Second Life Library 2.0 (http://infoisland.org) and those serving populations active in virtual environments should pick up a copy of this official, thorough full-color guide. The book walks beginners through getting started in Second Life and customizing their avatars; tells them where to go, what to see, and how to define their virtual existence; and ends with a discussion of the future and impact of Second Life. Its CD contains textures, templates, Avimator animation software, sample animations, videos, and a code for exclusive in-world content.
Keywords: Second Life (Game),Computer simulation,Shared virtual environments,Cuộc sống thứ hai (Trò chơi),Mô phỏng điện toán,Chia sẻ môi trường ảo